Conscientious objection, death and dying in terminal illnesses - Domínguez Márquez, Octaviano Humberto (Acta Bioethica, 2009)
This paper carries on a critical analysis of the figure of conscientious objection as an expression of the achievement of new spaces of liberty in societies in continuous evolution, that however, are still somewhat behind the times, specifically in the area of health. In addition, it links conscientious objection with aspects of the end of life and the tanatological process, in the ethical puzzles that modern technology presents by changing drastically the way we die.